Pre-ART program service delivery at a PHC facility level: access and retention of patients in care in the city of Johannesburg, South Africa - Nyasulu, Juliet Yauka-Kumwenda (My University, 2016)
Introduction South Africa (SA) has more than 6 million people infected with HIV, of whom 2.4 million have been initiated on Antiretroviral Treatment (ART). HIV positive non-pregnant women, and both women and men without tuberculosis and with a CD4 cell count of >500 cells/μl, were not eligible for ART initiation at the time of the study. These were transferred to a wellness (pre-ART) program for regular counselling and follow up. However, in SA, as in many other countries, previous data reported that there has been poor retention of HIV positive individuals prior to initiation on ART. This was particularly the case for youths and men. If people do not participate in a pre-ART program and are not regularly followed up, they often present for ART only when they are sick. Without an appropriate pre-ART program in PHC facilities, patients may end up delaying for ART initiation, leading to poor treatment outcome. Objective The objective of the study was to establish the existing gaps in pre-ART care service delivery and draw recommendations that would improve the quality of the delivery of pre-ART care and retain patients in care. Methodology This was a mixed method study conducted in the City of Johannesburg (CoJ). Both qualitative and quantitative data were collected through interviews, register and file audits and the District Health Information System (DHIS). A total of 2,018 participants were involved in this study through patient (73) and staff (12) interviews, an HCT register audit (1715), ART register and file audits (203), and consultative workshop with health services managers (15). In addition, we used records from DHIS data base for NIMART uptake before (6957) and after (13578) the NIMART roll-out in the CoJ. STATA version 12.0 was used to analyse quantitative data whilst qualitative data was analysed manually. Ethics approval was obtained from the University of the Witwatersrand Committee for Research on Human Subjects. Prior to each interview session, informed consent was obtained. Results The following pre-ART service delivery challenges were identified: long waiting times, multiple clinic visits, drug stock-outs, shortage of staff, unplanned disclosure of ones’ HIV+ status, poor staff attitudes to patients, length of time spent on documentation by service providers, and cost implications in accessing pre-ART care. Factors contributing to these challenges with potential solutions to overcome these were identified. The study also established that men (P=0.001) and youths (p=0.05) were less likely than their counterparts to collect their first CD4 cell count results. The majority of patients retained in pre-ART care did not access the available pre-ART care services and there was no difference in timely ART initiation between those who accessed pre-ART before ART initiation and those who did not – meaning that the current pre-ART care program was not working. However, being knowledgeable of the fact that an HIV+ person can lead a normal life through getting married and having an HIV- child was positively associated with retention in pre-ART care (p=0.001), i.e. attendance for 6 monthly monitoring. Rolling out NIMART into primary health care facilities in the CoJ significantly increased ART uptake, and reduced the workload in the referral facilities. Conclusion and recommendations Multiple interrelated pre-ART care service delivery challenges were identified in this study, consistent with other studies conducted in SA and elsewhere. This is a cause for concern as the provision of effective HIV services is compromised, leading to poor outcomes. In contrast, poor access and delayed ART initiation for patients retained in pre-ART care, established in this study, have not been reported previously. Therefore there is a need to improve access to quality pre-ART care services by those patients retained in pre-ART care. This can be attained by reducing pre-ART care access time through established innovations like Point of Care (POC) CD4 cell count collection and Central Chronic Medicines Dispensing and Distribution Programme (CCMDD), and addressing shortages of staff. In addition, raising patients’ awareness on available services, addressing poor staff attitudes, and strengthening linkages to pre-ART care after patients test HIV positive, would improve the uptake of pre-ART care especially among men and youths.
(MPH, BSC Community Health) Date: 20th April 2016